Thyroid Disorders that Impact Covid-19 A Multi-Center Study - Arifullah, Azam Khan, Muhammad Hussain Afridi, Syed Zafar Hasan, Khaddija Bibi (Pakistan Journal of Medical & Health Sciences, 2022)
COVID-1 has been linked to thyroid problems in the past. Hyperthyroidism is a disease that affects a wide range of people, from those with no symptoms to those who are experiencing symptoms. Objective: determination of this study is to look at mortality rates and clinic pathological aspects of various thyroid illnesses. Method: A Multi-center study conducted in NTH and HMC Hospital Peshawar between 2017 and May 2018 was culled for the study. Cases without informed consent and with a past of (thyroid disease) or thyroid surgery excluded. Chi-square and Fischer’s exact tests were employed to analyse thyroid lab findings for connection with clinical and pathological features. (SPSS version 22) be present the statistical analysis. In this experiment, a P-value of 0.05 was considered significant. Results: Ninety sample size had greater FT3 levels, and none reported having lower levels. Seventy-seventy percent (58.2 percent) reported greater FT4 levels, whereas nine percent (61.2 percent) reported lower FT4 levels. Anti-thyroperoxidase and anti-thyroglobulin antibodies were found in 6 (6.1 percent) and 6 (3.9 percent) participants, respectively. .Anti.TG (.P-value 0.002),(anti-TP ) (p-value 0.016) and free FT4 antibodies were shown to be statistically significant (p-value 0.005). Conclusion: Thyroid disorders were common in COVID-19 individuals. Time and spontaneous healing seem to be the hallmarks of thyroid dysfunction. Keywords: FT4 and FT3 anti-thyroglobulin and anti-thyroperoxidase